PENGARUH HARGA DAN TIPE RUMAH TERHADAP VOLUME PENJUALAN DI PERUMAHAN PESONA BOUGENVILLE PONOROGO - Kurniya Damayanti (FIPA : Forum Ilmiah Pendidikan Akuntansi, 2015)
The purpose of this research is (1) To know whether there is influence of price to sales volume in Pesona Perumahan Bougenville Ponorogo (2) To know whether there is influence of type to sales volume in Pesona Perumahan Bougenville Ponorogo (3) To know the existence of influence between price and type to sales volume in Bougenville Ponorogo Residential Charm. This research uses ekseperimen method. The population of the study is the entire citizen housing charm bougenville ponorogo. Respondents in this study a number of 45 respondents / consumers. In analyzing data using SPSS 16. Sampling using saturated sampling technique. Data collection techniques used questionnaires, observations, interviews. The data obtained were analyzed by statistical method. Data analysis technique used validity test, reliability test, multiple linear regression test, classical assumption test.The conclusion of this research is to show (1) Price has negative and significant relation with sales volume at Pesona Bougenville Ponorogo housing. (2) The type of house has a positive and significant relationship with the volume of sales on the housing Pesona Bougenville Ponorogo (3) Price and type of house together have a positive and significant relationship with the sales volume in the housing of Pesona Bougenville Ponorogo. The price offered will also affect the type of house that is sold.